2018
DOI: 10.1186/s12870-018-1502-3
|View full text |Cite|
|
Sign up to set email alerts
|

Two MYB transcription factors (CsMYB2 and CsMYB26) are involved in flavonoid biosynthesis in tea plant [Camellia sinensis (L.) O. Kuntze]

Abstract: BackgroundFlavonoids are secondary metabolites that play important roles in the entire tea plant life cycle and have potential health-promoting properties. MYB transcription factors (TFs) are considered potentially important regulators of flavonoid biosynthesis in plants. However, the molecular mechanisms by which MYB TFs regulate the flavonoid pathway in tea plant remain unknown.ResultsIn this study, two R2R3-MYB TFs (CsMYB2 and CsMYB26) involved in flavonoid biosynthesis in tea plant were investigated. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 39 publications
(48 reference statements)
1
29
0
Order By: Relevance
“…It has been reported that R2R3 MYB transcription factors act as important regulators in controlling the spatiotemporal biosynthesis of flavonoids during grape and apple fruit development [44,51]. Two MYB transcription factors, CsMYB2 and CsMYB26, were reported to be involved in flavonoid biosynthesis in tea (C. sinensis (L.) O. Kuntze) [52]. Additionally, GmMYB58 and GmMYB205 were demonstrated to be seed-specific activators for isoflavonoid biosynthesis in Glycine max [45].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that R2R3 MYB transcription factors act as important regulators in controlling the spatiotemporal biosynthesis of flavonoids during grape and apple fruit development [44,51]. Two MYB transcription factors, CsMYB2 and CsMYB26, were reported to be involved in flavonoid biosynthesis in tea (C. sinensis (L.) O. Kuntze) [52]. Additionally, GmMYB58 and GmMYB205 were demonstrated to be seed-specific activators for isoflavonoid biosynthesis in Glycine max [45].…”
Section: Discussionmentioning
confidence: 99%
“…The CsMYB4a could inhibit the promoter activity of five phenylpropanoid pathway genes (CsANR, CsLAR, CsCHS, Cs4CL, and CsC4H) and two shikimate pathway genes (CsAROC and CsAROF) [92]. Wang et al (2018) confirmed that CsMYB2 and CsMYB26 were involved in flavonoid biosynthesis by regulating the expression of CsF3 H and CsLAR in Camellia sinensis, respectively [93]. Huang et al (2015) cloned and isolated Epimedium sagittatum's two TFs (EsMYBA1 and EsMYBF1) and twelve structural genes.…”
Section: The Role Of Myb Tfs In the Biosynthesis Of Flavonoids Secondmentioning
confidence: 94%
“…Recently, flavonoids in tea (Camellia sinensis) were identified to mediate resistance against a crop destructive disease blister blight caused by Exobasidium vaxans [121]. The flavonoid biosynthesis in tea plants was regulated by CsMYB2/CsMYB26 that was directly bound to the promoters of CsF3'H and CsLAR, two flavonoid biosynthetic genes [104]. These two MYB TFs exhibited correlated inducible gene expression with their target genes upon pathogen infection [104].…”
Section: Myb Tfsmentioning
confidence: 99%
“…The flavonoid biosynthesis in tea plants was regulated by CsMYB2/CsMYB26 that was directly bound to the promoters of CsF3'H and CsLAR, two flavonoid biosynthetic genes [104]. These two MYB TFs exhibited correlated inducible gene expression with their target genes upon pathogen infection [104]. Moreover, three MYB TFs, AtMYB11, AtMYB12, and AtMYB111 were revealed to differentially regulate the flavonoid biosynthesis [97][98][99].…”
Section: Myb Tfsmentioning
confidence: 99%